H3K4me2 and WDR5 enriched chromatin interacting long non-coding RNAs maintain transcriptionally competent chromatin at divergent transcriptional units. Issue 18 (13th July 2018) - Subhash, Santhilal; Mishra, Kankadeb; Akhade, Vijay Suresh; Kanduri, Meena; Mondal, Tanmoy; Kanduri, Chandrasekhar
Abstract: Recently lncRNAs have been implicated in the sub-compartmentalization of eukaryotic genome via genomic targeting of chromatin remodelers. To explore the function of lncRNAs in the maintenance of active chromatin, we characterized lncRNAs from the chromatin enriched with H3K4me2 and WDR5 using chromatin RNA immunoprecipitation (ChRIP). Significant portion of these enriched lncRNAs were arranged in antisense orientation with respect to their protein coding partners. Among these, 209 lncRNAs, commonly enriched in H3K4me2 and WDR5 chromatin fractions, were named as active chromatin associated lncRNAs (active lncCARs). Interestingly, 43% of these active lncCARs map to divergent transcription units. Divergent transcription (XH) units were overrepresented in the active lncCARs as compared to the inactive lncCARs. ChIP-seq analysis revealed that active XH transcription units are enriched with H3K4me2, H3K4me3 and WDR5. WDR5 depletion resulted in the loss of H3K4me3 but not H3K4me2 at the XH promoters. Active XH CARs interact with and recruit WDR5 to XH promoters, and their depletion leads to decrease in the expression of the corresponding protein coding genes and loss of H3K4me2, H3K4me3 and WDR5 at the active XH promoters. This study unravels a new facet of chromatin-based regulation at the divergent XH transcription units by this newly identified class of H3K4me2/WDR5 chromatin enriched lncRNAs.